Evaluation of Complications Related to Exchange Transfusion due to Hyperbilirubinaemia in Newborns with or without Comorbidities (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Exchange transfusion (ET) is the first successful treatment introduced for severe neonatal jaundice considered to be a safe procedure but not risk free. Present study aimed to determine the complications related to exchange transfusion and to compare the incidence of severe complications between healthy and ill newborns.Methods: This cross sectional study was done in Neonatal Intensive Care Unit (NICU), Dhaka Shishu Hospital and Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, over 6 months from January to June 2010, included 50 newborns who underwent exchange transfusion due to hyperbilirubinaemia. Newborns with hyperbilirubinemia alone were classified as healthy, while hyperbilirubinaemia associated with other medical problems were classified as ill. Adverse events were analyzed and compared between two groups.Results: Out of 50 patients who underwent ET, 27 were healthy had jaundice only and 23 were ill. Most of the newborns with comorbidities (87%) developed at least one complication following exchange transfusion (p